Intermittent hypoxia in rats reduces activation of Ca(2+) sparks in mesenteric arteries - Jackson-Weaver, Olan (Am J Physiol Heart Circ Physiol, 2015)
Ca(+) sparks are vascular smooth muscle cell (VSMC) Ca(2+)-release events that are mediated by ryanodine receptors (RyR) and promote vasodilation by activating large-conductance Ca(2+)-activated potassium channels and inhibiting myogenic tone. We have previously reported that exposing rats to intermittent hypoxia (IH) to simulate sleep apnea augments myogenic tone in mesenteric arteries through loss of hydrogen sulfide (H(2)S)-induced dilation. Because we also observed that H(2)S can increase Ca(2+) spark activity, we hypothesized that loss of H(2)S after IH exposure reduces Ca(2+) spark activity and that blocking Ca(2+) spark generation reduces H(2)S-induced dilation. Ca(2+) spark activity was lower in VSMC of arteries from IH compared with sham-exposed rats. Furthermore, depolarizing VSMC by increasing luminal pressure (from 20 to 100 mmHg) or by elevating extracellular [K(+)] increased spark activity in VSMC of arteries from sham rats but had no effect in arteries from IH rats. Inhibiting endogenous H(2)S production in sham arteries prevented these increases. NaHS or phosphodiesterase inhibition increased spark activity to the same extent in sham and IH arteries. Depolarization-induced increases in Ca(2+) spark activity were due to increased sparks per site, whereas H(2)S increases in spark activity were due to increased spark sites per cell. Finally, inhibiting Ca(2+) spark activity with ryanodine (10 μM) enhanced myogenic tone in arteries from sham but not IH rats and blocked dilation to exogenous H(2)S in arteries from both sham and IH rats. Our results suggest that H(2)S regulates RyR activation and that H(2)S-induced dilation requires Ca(2+) spark activation. IH exposure decreases endogenous H(2)S-dependent Ca(2+) spark activation to cause membrane depolarization and enhance myogenic tone in mesenteric arteries.